P3_3 Fizzy Ocean! - Joshi, Rutambhara; Patel, Jessica; Patel, Poonam (Physics Special Topics, 2014)
This paper investigates the effect of the increasing levels of CO2 in the atmosphere, on it absorption into the oceans. We look at the temperature dependence of solubility of the CO2 and whether the increasing levels absorbed would reach a similar amount to soda water, and turn the oceans fizzy.